Socioeconomic status as a predictor of post-operative mortality and outcomes in carotid artery stenting vs. carotid endarterectomy - Baxi, Jigesh; Chao, Joshua C.; Dewan, Krish; Yang, NaYoung K.; Pepe, Russell J.; Deng, Xiaoyan; Soliman, Fady K.; Volk, Lindsay; Rahimi, Saum; Russo, Mark J.; Lee, Leonard Y. (Frontiers in Cardiovascular Medicine, 2024)
Background The association between low socioeconomic status (SES) and worse surgical outcomes has become an emerging area of interest. Literature has demonstrated that carotid artery stenting (CAS) poses greater risk of postoperative complications, particularly stroke, than carotid endarterectomy (CEA). This study aims to compare the impact of low SES on patients undergoing CAS vs. CEA. Methods The National Inpatient Sample (NIS) was queried for patients undergoing CAS and CEA from 2010 to 2015. Patients were stratified by highest and lowest median income quartiles by zip code and compared through demographics, hospital characteristics, and comorbidities defined by the Charlson Comorbidity Index (CCI). Primary outcome was in-hospital mortality. Secondary outcomes included acute kidney injury (AKI), post-operative stroke, sepsis, and bleeding requiring reoperation.Multivariable logistic regression was used to determine the effect of SES on outcomes. Results Five thousand four hundred twenty-five patients underwent CAS (Low SES: 3,516 (64.8%); High SES: 1,909 (35.2%) and 38,399 patients underwent CEA (Low SES: 22,852 (59.5%); High SES: 15,547 (40.5%). Low SES was a significant independent predictor of mortality [OR = 2.07 (1.25–3.53); p = 0.005] for CEA patients, but not for CAS patients [OR = 1.21 (CI 0.51–2.30); p = 0.68]. Stroke was strongly associated with low SES, CEA patients (Low SES = 1.5% vs. High SES = 1.2%; p = 0.03), while bleeding was with high SES, CAS patients (Low SES = 5.3% vs. High SES = 7.1%; p = 0.01). CCI was a strong predictor of mortality for both procedures [CAS: OR1.45 (1.17–1.80); p < 0.001. CEA: OR1.60 (1.45–1.77); p < 0.001]. Advanced age was a predictor of mortality post-CEA [OR = 1.03 (1.01–1.06); p = 0.01]. While not statistically significant, advanced age and increased mortality trended towards a positive association in CAS [OR = 1.05 (1.00–1.10); p = 0.05]. Conclusions Low SES is a significant independent predictor of post-operative mortality in patients who underwent CEA, but not CAS. CEA is also associated with higher incidence of stroke in low SES patients. Findings demonstrate the impact of SES on outcomes for patients undergoing carotid revascularization procedures. Prospective studies are warranted to further evaluate this disparity.